Розвиток інноваційної сфери як запорука підвищення рівня конкурентоспроможності країни - Іванова, В. Б. (ХНУРЕ, 2017)
The article deals with the process of interaction between the indicator of the country's competitiveness and the level of development of the innovation sphere. Common features of these indicators are revealed. The dynamics of the change in the indicators of the GCI and The Bloomberg Innovation Index for Ukraine for the last 6 years has also been analyzed. The leading role of innovations in increasing the country's competitiveness in the international market was determined.
Keywords: конкурентоспроможнстьі країни; розвиток інноваційної сфери